Improving Diabetic Retinopathy Fundus Image Quality Using Dynamic Sparse Representation and Dilated Convolutional Networks - Basreddy, Veerendra; Veerashetty, Sachinkumar (Engineering, Technology & Applied Science Research, 2026)
In recent years, there has been an increase in Diabetic Retinopathy (DR). In addition, the images used for the detection of DR are not of good quality. This study focuses on improving the quality of DR fundus images by proposing an image enhancement approach. Specifically, this work presents a Dynamic Sparse Representation (DSR) approach that combines Convolution layers (Conv), Rectified-Linear-Unit (ReLU), and Dilated-Convolution methods for preprocessing. To further improve image quality, DSR utilizes a dictionary approach during the training phase. Before testing, Additive White Gaussian Noise (AWGN) is induced in the input images to simulate real-world noise conditions. In the testing phase, noisy images are processed to remove noise and enhance image quality. The proposed DSR method was evaluated on the MESSIDOR and EyeQ datasets using the following metrics: Peak Signal-to-Noise Ratio (PSNR), Structural Similarity Index Measure (SSIM), and Mean Squared Error (MSE). For the EyeQ and MESSIDOR datasets, DSR achieved 37.82 PSNR, 0.94 SSIM, 0.0316 MSE, and 36.85 PSNR, 0.93 SSIM, and 0.0431 MSE, respectively. The findings show that the proposed DSR approach achieved better performance compared to other approaches.